Beach-Hub Creative: A Blue Marketing and Digital Finance Strategy for Empowering Coastal Youth - Pathrisye Richendi Limba; Venezia Thalia Metekohy; Fredy Hendry Louhenapessy; Hansen Hein Rumtutuly; Simon Hendrik Leasa (Jurnal Altifani Penelitian dan Pengabdian kepada Masyarakat, 2026)
Coastal tourism areas offer significant opportunities for strengthening local economies through the development of tourism-based creative enterprises. However, in many coastal communities this potential has not been fully optimized due to several structural and capacity-related challenges. Limited entrepreneurial literacy among local youth, low utilization of digital technologies in business activities, and inadequate financial management practices among small enterprises often hinder the transformation of tourism resources into sustainable economic opportunities. Considering that young people represent an important driver of innovation and local economic development, strengthening their entrepreneurial capacity becomes an essential step in maximizing the potential of coastal tourism. This study aims to examine the effectiveness of the Beach-Hub Creative program as a community-based empowerment model designed to enhance youth entrepreneurial capacity in coastal tourism areas. The program integrates blue marketing strategies with basic digital financial management practices to support the development of creative and sustainable businesses. The research employed a participatory approach through educational sessions, practical training, and guided practice on digital marketing, product branding, and the use of simple digital financial recording tools. The findings indicate that participants experienced notable improvements in their understanding of digital promotion strategies, product branding, and more structured financial management practices. Moreover, the program increased participants’ confidence and motivation to initiate tourism-based creative businesses. These results suggest that the Beach-Hub Creative model can contribute to strengthening youth entrepreneurship and promoting sustainable economic development in coastal tourism communities.